A comprehensive review of chemokine CXC17 (VCC1) in cancer, infection, and inflammation. (10th July 2022) - Gowhari Shabgah, Arezoo; Jadidi‐Niaragh, Farhad; Ebrahimzadeh, Farnoosh; Mohammadi, Hamed; Askari, Elham; Pahlavani, Naseh; Malekahmadi, Mahsa; Ebrahimi Nik, Maryam; Gholizadeh Navashenaq, Jamshid
Abstract: A crucial component of the immune system are chemokiness. Chemokine's dysregulation has been linked to a number of pathological diseases. Recently, CXCL17, a chemokine belonging to the CXC subfamily, was identified. With regard to a number of physiological conditions and disorders, CXCL17 either has homeostatic or pathogenic effects. Some research suggests that CXCL17 is an orphan ligand, despite the fact that G protein‐coupled receptor (GPR) 35 has been suggested as a possible receptor for CXCL17. Since CXCL17 is primarily secreted by mucosal epithelia, such as those in the digestive and respiratory tracts, under physiological circumstances, this chemokine is referred to as a mucosal chemokine. Macrophages and monocytes are the cells that express GPR35 and hence react to CXCL17. In homeostatic conditions, this chemokine has anti‐inflammatory, antibacterial, and chemotactic properties. CXCL17 promotes angiogenesis, metastasis, and cell proliferation in pathologic circumstances like malignancies. However, other studies suggest that CXCL17 may have anti‐tumor properties. Additionally, studies have shown that CXCL17 may have a role in conditions such as idiopathic pulmonary fibrosis, multiple sclerosis, asthma, and systemic sclerosis. Additionally, deregulation of CXCL17 in some diseases may serve as a biomarker for diagnosis and prognosis. Clarifying the underlying mechanism of CXCL17's activity in homeostatic and pathological situations may thus increase our understanding of its role and hold promise for the development of novel treatment strategies.